Comparative Study of Multilevel Converters using DQ Current Control - José Vicente; Agostinho Rocha (U.Porto Journal of Engineering)
This paper presents a comprehensive comparative analysis of different multilevel converter topologies, including 2-level, Neutral Point-Clamped (NPC), Cascaded H-Bridge (CHB), and T-Type converters using the DQ current control strategy. The study aims to evaluate the performance of these topologies concerning current Total Harmonic Distortion (THD) and ripple in the direct and quadrature components of the current.